Polycomb silencers control cell fate, development and cancer - Sparmann, Anke; van Lohuizen, Maarten (Nature reviews. Cancer, 2006)
Key Points Epigenetic gene silencing is an important mechanism for the loss of gene function and collaborates with genetic mutation in the initiation and progression of human cancer. Polycomb group (PcG) proteins regulate epigenetically mediated transcriptional silencing. They are involved in the maintenance of embryonic and adult stem cells and have been implicated in cancer development. PcG-mediated repression of key tumour-suppressor pathways, as well as their role in the regulation of stem cell maintenance might contribute to their oncogenic function. The recent global identification of PcG target genes provides the first insights into the mechanisms that govern stem cell maintenance and imply a dynamic regulation of PcG function during differentiation. Polycomb group (PcG) proteins are epigenetic gene silencers that are implicated in neoplastic development. How do PcGs regulate cellular identity, and how might these functions be relevant during tumorigenesis? Polycomb group (PcG) proteins are epigenetic gene silencers that are implicated in neoplastic development. Their oncogenic function might be associated with their well-established role in the maintenance of embryonic and adult stem cells. In this review, we discuss new insights into the possible mechanisms by which PcGs regulate cellular identity, and speculate how these functions might be relevant during tumorigenesis.